CORN SPAGHETTI RICA-RICA SAUCE (COTTI CASA) AS A PASTA DIVERSIFICATION BASED ON LOCAL FOOD - Ichda Chayati, Tri Haryanti (Prosiding Pendidikan Teknik Boga Busana, 2020)
Many cereals grow in Indonesia such as rice, wheat, durum wheat, rye, and so on. One of the local foodbased cereals is corn. This study aims to 1find a recipe for corn spaghetti products, 2knowing the community acceptance of corn spaghetti products, and 3knowing the nutritional content of corn spaghetti products. The research uses the Research and Development (R & D) method with the 4D development model (Define, Design, Develop, and Disseminate). In this study, the product of corn spaghetti named Cotti Casa (Corn Spaghetti Ricarica Sauce) with the composition variable of corn flour used was 20%, 30%, and 40%. Data were analyzed by paired T-test and qualitative descriptive. The results showed that corn spaghetti products that could be accepted by the community were in the ratio of corn flour and wheat flour, which was 20%: 80% with criteria in terms of color, aroma, texture, and taste in a very popular way. Besides the nutritional content contained in corn spaghetti products include water content 63.56%, ash 0.37%, protein 7.31%, fat 5.01%, crude fiber 3.57%, carbohydrate 20.18 &, and energy 154.26 kal / g. Keywords: Spaghetti, corn, corn flour, rica-rica